Pengarusutamaan Pengurangan Resiko Bencana (PRB) Di Daerah Rawan Bencana Kabupaten Sleman - Herpita Wahyuni; Sakir Sakir (Universitas Muhammadiyah Ponorogo, 2021)
This research aims to determine the Merapi volcano disaster risk reduction (DRR) mainstreaming in Cangkringan District, Sleman Regency. DRR mainstreaming is urgently needed in Cangkringan District because the areas most affected by the threat of the eruption of Mount Merapi. This research adopts the design of a case study that will study and analyze DRR mainstreaming through structural and non-structural development in depth with primary data through interviews and secondary data through documentation. Data collection techniques sourced from interview data were 14 sources, namely: Sleman Regency Regional Disaster Management Agency, Sleman Regency Regional Development Planning Agency, Cangkringan District, Village Heads in Cangkringan, Cangkringan Residents, Volcano Disaster Community, Sleman Regency Land and Spatial Planning Agency , Department of Public Works, Housing, and Settlement Areas of Sleman Regency, and secondary data sourced from the documentation of the implementation of the DRR disaster-prone areas of Mount Merapi, Cangkringan District, Sleman Regency. Data analysis technique with CAQDAS (Computer-assisted Qualitataive Data, Analysis Software) namely Nvivo which is useful and effective in helping qualitative research efficiently, helping the consumption of logic and research design and providing facilities for analyzing content. Features that are used by NVIVO in the research analysis include: Create New Project, which includes data in the form of literature about the risk reduction of Mount Merapi in Cangkringan District, Import Feature which functions to enter research data in the form of interviews and documentation data, Feature node functions to classify data in the research on the coding process, the Crosstab feature obtained the results of calculations between all data that had been found regarding the Mount Merapi DRR in Cangkringan District. The study found that the implementation of spatial planning in Cangkringan District was understood by the residents of Cangkringan. Development arrangements in Cangkringan Subdistrict still found illegal development due to inadequate economic factors. The infrastructure development in Cangkringan Subdistrict was quite well implemented. The disaster preparedness schools in Cangkringan Subdistrict were evenly distributed. The training is given from both government and non-government, which is once a year in the form of disaster simulation. Counseling activities in an effort to reduce disaster risk are carried out once a year and obtain information needed by residents in the volcano prone area. Based on the results of the study concluded under the implementation of DRR in the District of Cangkringan, Sleman Regency has been carried out quite effectively and provides understanding for residents of Cangkringan in solving the financial problems of Mount Merapi and the rules about vulnerable areas, III. with a maximum due to several economic factors that are still low. The government needs to be able to increase supervision and further research can be done to find out the implementation of DRR in disaster prone areas in Cangkringan District, Sleman Regency.